Taklim Keluarga Bagi Pendidikan Akhlak Anak di Kalangan Jamaah Tabligh di Kota Bengkulu - Hidayat, Wahyu; Margaretha, Lydia (UIN Fatmawati Sukarno Bengkulu, 2025)
This research aims to deeply examine the role of family taklim (religious instruction) in facilitating and shaping children's moral education (akhlak) within the Jamaah Tabligh community in Bengkulu City. This study utilized a qualitative field research method in the form of a case study with a descriptive-analytical approach, seeking to interpret the phenomenon holistically. The research population included all Jamaah Tabligh families actively conducting taklim, while the sample consisted of 5-7 core families (parents and children) selected through a purposive sampling technique. Data collection was carried out using in-depth interviews, participant observation, and documentation study. Data analysis was applied using the Miles and Huberman interactive qualitative analysis model, which includes data reduction, data display, and conclusion drawing. The results indicate that family taklim acts as an effective hidden curriculum in transferring the values of amar ma'ruf nahi munkar (enjoining good and forbidding wrong), creating a disciplined moral environment, and instilling Islamic morality in children. The recommendation from this study is the necessity of optimizing taklim material through the integration of contemporary issues and the development of taklim e-modules.